Evaluasi Kinerja Jalan Akibat Parkir Pada Kantor Walikota, Perkantoran dan Pertokoan Pada Jalan Ahmad Yani Kota Makassar - Hayatul, Hayatul (Jurnal Penelitian Teknik Sipil Konsolidasi, 2024)
Indonesia is a country with a fairly rapid private vehicle ownership. This is not in line with the increase in parking space as a parking lot. Shopping centers often experience problems with the availability of parking spaces so that it is not uncommon for the shoulder of the road to be used as a parking area, therefore it is necessary to identify road performance and parking characteristics on the Ahmad Yani road, Makassar City. Road performance analyzed is, Traffic Volume, Capacity, Speed, Parking Volume, Parking Accumulation. From the results of observations made on Jalan Ahmad Yani, Makassar City for 1 week, it was found that the largest vehicles passing on Jalan Ahmad Yani Makassar City were 18736 vehicles on Sundays. The largest parking volume for cars is 68 vehicles and for motorcycles 26 vehicles. The capacity after using the shoulder of the road as a parking lot is 11007 pcu/hour.